Analisis Penerapan Audit Sumber Daya Manusia Untuk Meningkatkan Efektivitas Pengendalian Internal Pada PDAM Tirtanadi Medan - Seftiani, Asti; Siregar, Ratih Anggraini; Masyitah, Emi (ProBisnis : Jurnal Manajemen, 2025)
This research is motivated by the importance of human resource (HR) management in facing business competition. The success of a company largely depends on the quality of its human resources; therefore, an HR audit is needed to identify gaps in practices, policies, and procedures, as well as to improve the effectiveness of internal control. Initial observations at PDAM Tirtanadi Medan revealed noncompliance among employees with standard operating procedures (SOP), such as smoking during working hours, loss of documents, failure to attend training, and not wearing uniforms or identification badges. This study employs a descriptive qualitative approach with a case study method. Data were obtained through literature review, observation, interviews, and documentation, and analyzed using NVivo. The findings indicate that the main causes of noncompliance are weak supervision and the lack of strict sanctions. The solutions implemented by the company include disseminating SOPs, providing easy access to regulations, and enforcing sanctions in accordance with the severity of violations.